The bacterial alkyltransferase-like (eATL) protein protects mammalian cells against methylating agent-induced toxicity - Tomaszowski, Karl-Heinz; Aasland, Dorthe; Margison, Geoffrey P.; Williams, Emma; Pinder, Sarah I.; Modesti, Mauro; Fuchs, Robert P.; Kaina, Bernd (DNA repair, 2015)
In both pro- and eukaryotes, the mutagenic and toxic DNA adduct O6-methylguanine (O6MeG) is subject to repair by alkyltransferase proteins via methyl group transfer. In addition, in prokaryotes, there are proteins with sequence homology to alkyltransferases, collectively designated as alkyltransferase-like (ATL) proteins, which bind to O6-alkylguanine adducts and mediate resistance to alkylating agents. Whether such proteins might enable similar protection in higher eukaryotes is unknown. Here we expressed the ATL protein of Escherichia coli (eATL) in mammalian cells and addressed the question whether it is able to protect them against the cytotoxic effects of alkylating agents. The Chinese hamster cell line CHO-9, the nucleotide excision repair (NER) deficient derivative 43-3B and the DNA mismatch repair (MMR) impaired derivative Tk22-C1 were transfected with eATL cloned in an expression plasmid and the sensitivity to N-methyl-N′-nitro-N-nitrosoguanidine (MNNG) was determined in reproductive survival, DNA double-strand break (DSB) and apoptosis assays. The results indicate that eATL expression is tolerated in mammalian cells and conferes protection against killing by MNNG in both wild-type and 43-3B cells, but not in the MMR-impaired cell line. The protection effect was dependent on the expression level of eATL and was completely ablated in cells co-expressing the human O6-methylguanine-DNA methyltransferase (MGMT). eATL did not protect against cytotoxicity induced by the chloroethylating agent lomustine, suggesting that O6-chloroethylguanine adducts are not target of eATL. To investigate the mechanism of protection, we determined O6MeG levels in DNA after MNNG treatment and found that eATL did not cause removal of the adduct. However, eATL expression resulted in a significantly lower level of DSBs in MNNG-treated cells, and this was concomitant with attenuation of G2 blockage and a lower level of apoptosis. The results suggest that eATL confers protection against methylating agents by masking O6MeG/thymine mispaired adducts, preventing them from becoming a substrate for mismatch repair-mediated DSB formation and cell death.